Development and performance evaluation of epoxy resin system for repairing agent. Issue 22 (18th February 2022) - Liu, Shi; Liu, Wenming; Qi, Ben; Lin, Zhihui; Li, Pengpeng; Wu, Chaoming; Zhang, Qingchang; Hu, Miaomiao; Guo, Jintang
Abstract: In the development of unconventional oil and gas resources, such as offshore oil, high pressure oil and sour wells, casing‐casing annulus pressure is a common problem. To prevent casing‐casing annulus pressure, bisphenol F epoxy resin, dicyandiamide hardener SH‐500A and urea accelerator SH‐A100 are added to develop an epoxy resin system. The thickening time and the compressive strength at 90°C are used as the main evaluation indexes. The optimal formulation was found to be as follows: bisphenol F epoxy resin NPEF‐170 with 20 wt% of diluent benzyl glycidyl ether, 9.0 wt% of hardener dicyandiamide and 0.5–0.4 wt% of urea accelerator SH‐A100. The experimental results showed that the initial consistency of the epoxy resin system is less than 30 Bc, the thickening time is 3–4 h, and the compressive strength at 90°C is above 27 MPa, which meet the requirements of on‐site construction. Abstract :